Species diversity and phylogeny of fleas of small terrestrial mammals in the forests of the Central Highlands of Madagascar - Harimalala, Mireille; Miarinjara, Adelaïde; Duchemin, Jean-Bernard; Ramihangihajason, Tojo; Boyer, Sebastien (Zootaxa, 2018)
Fleas are holometabolous insects forming the order of Siphonaptera. Some studies have been carried out on biology and systematic of Malagasy fleas, but little is known about their phylogenetic relationships. In this study, we focused on flea species occurring in the forests of the Central Highlands and also, on the determination of their phylogenetic relationships. Three families, five genera and thirteen species were identified. The family Pulicidae includes four species (Centetipsylla madagascariensis Rothschild, Synopsyllus fonquerniei Wagner & Roubaud, S. estradei Klein and S. robici Klein); Leptopsyllidae has eight species (Paractenopsyllus vauceli Klein, P. petiti Klein, P. viettei Klein, P. grandidieri Klein, P. goodmani Duchemin, P. rouxi Duchemin, P. raxworthyi Duchemin & Ratovonjato and Tsaractenus rodhaini Duchemin), and Ctenophtalmidae one species (Dinopsyllus brachypecten Smit). All are endemic to Madagascar and each differs geographically. Flea phylogenetic relationships were inferred using four molecular markers (ITS2, mtCOII, 16SrRNA and 12S rRNA) and using Neighbor-Joining, Maximum Parsimony and Bayesian methods with addition of Genbank sequences of exotic species. The Family Pulicidae was monophyletic while the families Leptopsyllidae and Ctenophtalmidae were paraphyletic. Malagasy fleas are homogeneous and all species adhere to current classification schemes.